2023
DOI: 10.1007/s40801-023-00359-1
|View full text |Cite
|
Sign up to set email alerts
|

Dermatology Life Quality Index in Patients with Psoriasis Treated with Biologic Versus Non-biologic Treatment in Malaysia: A Retrospective Cross-Sectional Study

Abstract: Background Psoriasis imposes a substantial burden on patients’ social, emotional, physical, and family life. Although psoriasis has no complete cure, various treatments are available to control its symptoms and improve a patients’ quality of life. Objective We aimed to compare the effectiveness of biologic versus non-biologic treatments on health-related quality of life among patients with psoriasis in Malaysia. Methods This retrospective cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Показатели ДИКЖ обычно коррелируют с данными оценки по PASI и результатами применения других шкал оценки качества жизни. Большинство научных публикаций посвящено применению ДИКЖ в рамках клинических исследований, в том числе анализу эффективности биологической тера- Robinson, 2023 [25] необходимости назначения современного лекарственного лечения большему числу пациентов [1,33]. Таким образом, возможные недостатки ДИКЖ могут быть устранены путем проведения дополнительных клинических исследований.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Показатели ДИКЖ обычно коррелируют с данными оценки по PASI и результатами применения других шкал оценки качества жизни. Большинство научных публикаций посвящено применению ДИКЖ в рамках клинических исследований, в том числе анализу эффективности биологической тера- Robinson, 2023 [25] необходимости назначения современного лекарственного лечения большему числу пациентов [1,33]. Таким образом, возможные недостатки ДИКЖ могут быть устранены путем проведения дополнительных клинических исследований.…”
Section: Discussionunclassified
“…В практике оценки эффективности биологической терапии (начало терапии или смена биологического препарата) показатели ДИКЖ оказываются полезными для оценки субъективных жалоб пациента, не включенных в шкалу PASI [24]. В крупном малазийском исследовании эффективности биологической терапии в отношении качества жизни (КЖ) по ДИКЖ изучались регистрационные записи по взрослым пациентам (Robinson et al [25]). В анализ были включены 15 238 пациентов.…”
Section: роль дикж в оценке эффективности новой биологической терапииunclassified
See 1 more Smart Citation
“…7,8 These clinical improvements are paralleled by enhancements in patientreported outcome measures, including the Dermatology Life Quality Index (DLQI). [8][9][10][11][12][13][14][15][16][17] However, it is imperative to note that achieving clear skin does not guarantee an optimal quality of life for all patients. Several studies have revealed that approximately 20% of patients with clear skin still report a negative impact of psoriasis on their quality of life, as indicated by DLQI scores exceeding 1.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in biologic treatments have revolutionized psoriasis management, offering patients the potential for near or complete skin clearance 7,8 . These clinical improvements are paralleled by enhancements in patient‐reported outcome measures, including the Dermatology Life Quality Index (DLQI) 8–17 …”
Section: Introductionmentioning
confidence: 99%